Application of a newly developed radial directional electron probe to the edge unidirectional electron current measurement in EAST. (December 2021) - Liu, S.C.; Liang, Y.; Yan, N.; Liao, L.; Wei, W.Y.; Meng, L.Y.; Chen, L.; Xu, S.; Zhao, N.; Chen, R.; Hu, G.H.; Li, Y.L.; et al.
Highlights: A newly developed radial directional electron probe (DEP) has been applied on EAST. DEP can measure the amplitude and structure of SOL unidirectional electron current. This is the first application of DEP to unidirectional electron current in experiment. The SOL unidirectional electron current driven by LHW is directly measured. Abstract: A newly developed radial directional electron probe (DEP) has been applied to the unidirectional electron current measurement on EAST tokamak. The DEP consists of two radial arrays of channels which have opposite directions and align along the local magnetic field line. Each radial array has 6 holes with a radial interval of 5 mm. Every channel has a hole with 0.5 mm radial width, 3 mm depth and 15° poloidal opening angle. The graphite collector embedded inside the hole is biased to positive potential to repel low energy ions, and high energy ions are blocked by the hole surface because their Larmor radii are larger than the radial width of hole. In consequence, the ion current collected by the DEP collector can be ignored in contrast with the electron current, as demonstrated by the I - V characteristics in a DEP commissioning experiment. The difference of collected current between two opposite channels signifies the unidirectional electron current in the flux tube. In a lower hybrid wave (LHW) modulation experiment, the amplitude and radial structure of unidirectional electron current induced by LHW is measured directly by this radial DEP array, and the LHW filament current covers over 20 mm radial region with a maximum of 20 A/cm 2 .